Mechanism of visible light enhanced catalysis over curcumin functionalized Ag nanocatalysts - Verma A.; Shukla M.; Kumar S.; Pal S.; Sinha I. (My University, 2025)
There is little research on the visible light photocatalytic properties of the hybrids of plasmonic metals and organic molecules (OM) with the HOMO-LUMO gap in the visible range. Here, we investigate the mechanism of the visible light enhanced reduction of p-nitrophenol (PNP) by glycerol (a green reductant) at ambient temperature over curcumin functionalized Ag nanoparticles (c-AgNPs). The catalytic activity got significantly boosted under visible light irradiation. Reaction kinetics indicated that the catalytic mechanism followed under visible light and in the dark were different. DFT calculations showed that in the ground state, the HOMO resides on Ag while the LUMO is on the curcumin part of the composite. TD-DFT calculations demonstrated the transfer of charge from Ag to curcumin on photo-excitation. Based on this information, we propose a mechanism for understanding the role of curcumin in this photocatalytic phenomenon. © 2020 Elsevier B.V.